Influence of Capital, Business Duration, Education Level, and Gender on Business Income - Refi Mariska; Imsar Imsar; Budi Dharma (Jurnal Kewirausahaan dan Bisnis, 2024)
Income refers to the total sum of money that a family or individual receives monthly in exchange for services; it can also be defined as the profitability of a business. Understanding company income is crucial for business owners who want to track financial performance. This study examines the impact of capital, business duration, gender, and educational attainment on the revenue generated by businesses in Sukasari Village, Pegajahan District, Serdang Bedagai Regency. The research employs a quantitative method, utilizing questionnaires and interviews for data collection. A sample of sixty respondents was analyzed using path analysis, with data processed through the SmartPLS program. The results indicated that capital, length of operation, education level positively and significantly impacted income, whereas gender did not. This suggests that gender is not a reliable predictor of a company's income, and no evidence of gender bias was found in the data. However, capital, business duration, education level, and gender collectively positively and significantly affected company income. The findings suggest that strategies to enhance business income should focus on increasing capital investment and ensuring operational sustainability, education level as these factors are more critical to profitability than demographic variables.Keywords: business income; capital investment; education impact; gender